Flashback as a Rhetorical Online Battleground: Debating the (Dis)guise of the Nordic Resistance Movement. (January 2019) - Blomberg, Helena; Stier, Jonas
The right-wing Swedish Nordic Resistance Movement (NRM) is increasingly active on social media. Using discursive psychology, this text explores the rhetorical organization of text and rhetorical resources used on the Swedish online forum Flashback. The aim is to reveal and problematize truth claims about NRM made by antagonists and protagonists. Questions are (1) how and what do NRM antagonists and protagonists convey in Flashback posts about NRM, and its ideology and members? (2) how do NRM antagonists and protagonists make truth claims about NRM in Flashback posts? The empirical material consisting of 1546 Flashback posts analyzed to identify typical discussions on "NMR's true nature"; accomplished social actions stemming from the posts. Findings show that the Flashback thread can be understood as being a rhetorical battle that concerns the "truth" about NRM, where a variety of rhetorical resources are used to render statements credibility and those involved legitimacy.